Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

X-elles: le sexe par les femmes - Millet, Catherine..; Leydier, Richard 19.... (Art Press, 2004)
"Adresses Internet p. 112-113."Contient : Editorial : un raz de marée, par Catherine Millet et Richard Leydier, p. 5-7. Chapitre 1 : Elles débarquent! : L'acte pour l'art, par Louis-José Lestocart, p. 10-14 ; Bandes de femmes, par Bernard Joubert, p. 15-21 ; Éros féminin surréel, par Victoria Combalía, p. 22-27 ; Ellen von Unwerth. Naughty Girls!, interview par Richard Leydier, p. 28-31 ; Organes et orgasmes. Sur quelques chanteuses sexy, par Stéphane Pencréac'h, Stéphane Ruiz et Richard Leydier, p. 32-36; Dans le train fantôme de Catherine Breillat, témoignages recueillis par Brigitte Ollier, p. 37-40 ; Clarisse Hahn. La sexualité dans le tissu de la vie, interview par Catherine Millet et Louis-José Lestocart, p. 41-44 ; Portfolio #1 : Aude du Pasquier-Grall, Sonia Koumskoff-Raissi, Nicole Tran Ba Vang, Ornela Vorpsi, Friedl Kubelka, Anne Dion., p. 45-50. Chapitre 2 : Un autre porno : Angela, Loulou et les autres ... Quand les femmes prennent la caméra, par Stéphane Ruiz, p. 52-60 ; Monika Treut. Female Misbehavior, par Thibaut de Ruyter, p. 61-65 ; Maria Beatty. De la surface à la profondeur, par Catherine Corringer, p. 66-70 ; Shu Lea Cheang. Un genre en soi, Interview par Louis-José Lestocart, p. 71-74 ; Il y a une vie après le X : Brigitte, Tabatha, Ilona et Traci, par Laurent Goumarre, p. 75-80 ; Ovidie, plus librement, interview par Laurent Goumarre, p. 81-84 ; Portfolio #2 : Kiki Seror, Virginie Boursette, Béatrice Cussol, Bettina Rheims, Pascale Lafay, Diana Michener, p. 85-90. Chapitre 3 : Autoportraits : Lamia Ziadé. "Je suis une vraie petite femme d'intérieur", interview par Brigitte Ollier, p. 92-96 ; Chloë des Lysses. Une femme en danger, interview par Richard Leydier, p. 97-101 ; Madeleine Berkhemer. Élastique, érotique, par Alix Rozès, p. 102-105 ; Elke Krystufek. Le miroir qui met à nu, interview par Joerg Bader, p. 106-109 ; La pornographie, to remember, par Judith Brouste, p. 110-111 ; Les femmes sur le Web, par Chloë des Lysses, p. 112-113.
Keywords: 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; europe; france; har4600; histoire de l'art; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques

Corps, sexe et art: dimension symbolique - Pearl, Lydie (Nouvelles études anthropologiques, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques